Effect of filtration in functionalized and non-functionalized CNTs and surface modification of fibers as an effective alternative approach. (1st June 2016) - Jiménez-Suárez, A.; Campo, M.; Prolongo, S.G.; Sánchez, M.; Ureña, A.
Abstract: Fabrication of multiscale composites by the addition of CNT in epoxy matrices as previous step to the impregnation process leads to several manufacturing difficulties associated to filtration effects and viscosity increments. These effects have been analyzed finding a relation between the type of CNT and the dispersion degree with the change in the rheological behavior and the heterogeneity of the mechanical properties. This heterogeneity is associated to filtration effects of the nanoreinforcement. Modification of the carbon fibers by a nanoreinforced sizing has been presented as an alternative, obtaining homogeneous composites and avoiding the filtration effects. These multiscale composites have higher electrical and interlaminar mechanical properties.